Carbon mineralization in coastal wetlands : from litter decomposition to greenhouse gas dynamics - Ouyang, Xiaoguang; Lee, Shing-Yip; Lai, Derrick Y. F.; Marchand, Cyril (Estuarine and coastal sciences series ;, 2022)
"Carbon Mineralization in Coastal Wetlands: From Litter Decomposition to Greenhouse Gas Dynamics fills the current knowledge gap in carbon mineralization, providing a balanced view of the carbon dynamics of coastal wetlands. This book provides a holistic treatment of carbon mineralization, from the contributions of litter/root decomposition pathways to carbon mineralization and the processes and sources of greenhouse gas production. This book compares carbon mineralization in coastal wetlands and highlights differences in carbon dynamics. As studies on blue carbon have strongly emphasized the storage potential of coastal wetlands, this book serves as an ideal resource on the topics discussed."--